Points of entry dynamics: understanding the cross-border threats for Ebola virus disease and COVID-19 in Ghana using a logic model approach - John K. Duah; Oluwatosin Dotun-Olujinmi; James A. Johnson; Richard G. Greenhill (AOSIS, 2023)
Background: The influx of people across the national borders of Ghana has been of interest and concern in the public health and national security community in recent times due to the low capacity for the prevention and management of epidemics and other public health risks. Although the international health regulations (IHR) stipulate core public health capacities for designated border facilities such as international airports, seaports, and ground crossings, contextual factors that influence the attainment of effective public health measures and response capabilities remain understudied. Objective: This study aims to assess the relationship between contextual factors and COVID-19 procurement to help strengthen infrastructure resources for points of entry (PoE) public health surveillance functions, thereby eliminating gaps in the design, implementation, monitoring, and evaluation of pandemic-related interventions in Ghana. Methods: This study employed a mixed-methods design, where quantitative variables were examined for relationships and effect size interactions using multiple linear regression techniques and the wild bootstrap technique. Country-level data was sourced from multiple publicly available sources using the social-ecological framework, logic model, and IHR capacity monitoring framework. The qualitative portion included triangulation with an expert panel to determine areas of convergence and divergence. Results: The most general findings were that laboratory capacity and Kotoka International Airport testing center positively predicted COVID-19 procurement, and public health response and airline boarding rule negatively predicted COVID-19 procurement. Conclusion: Contextual understanding of the COVID-19 pandemic and Ebola epidemic is vital for strengthening PoE mitigation measures and preventing disease importation.